The effect of water and citric acid on sago starch bio-plastics - Ahmad, Zuraida; Yusof, Yusliza; Anuar, Hazleen; R., Mohd Khairul Muhaimin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Starch is a biodegradable polymer produced in abundance from many renewable resources. This study examined the influence of citric acid (0-40% w/wt%) ) and water (0-40% w/wt%) as secondary additive and glycerol as plasticizer on the mechanical properties of bio-plastic starch (BPS) from Malaysian sago. The CA content varies from 0 to 40 w/wt% while water was also varied from 0 to 40 w/wt%. FT-IR spectroscopy showed that acid citric improve the properties of BPS and water give negative effects to the carbon hydrogenbond. It is obvious that the addition of the CA at 30 wt/wt% improve the mechanical property of BPS to more than 40% compare to the addition of water.